Kecerdasan Seksual dalam Perspektif Al-Quran - Supriadi, Akhmad (Jurnal Studi Agama dan Masyarakat, 2009)
The study explores about the sexual intelligence based on Al-Quran perspective. Philosophically, it begins from Al-Muminun verses 1-6. It attempts to elaborate the Quran paradigm comprehensively on sexual intelligence by raising three main problems, they are: the concept of sexual intelligence, the urgency of sexual intelligence, and the Quran guidance in establishing the sexual intelligence. To observe of the three problems above, the thematic interpretation method was applied using linguistic, psychological, hermeneutic and semiotic approaches. The findings of the study were as follows. First, the sexual intelligence was an accumulation and integration of all the intelligence elements: intellectual, emotional and spiritual. Second, the sexual intelligence had broadly urgency and it gave strong influence to the whole aspects of life such as morally, psychologically, sociologically, biologically, theologically, and spiritually. Third, to establish the sexual intelligence, a Muslim had to take care of his or her sight, keep his or her genitals, get adequate knowledge about sex and avoid from the pornographic media.